Webrooming and Pure Online Shopping Behavior of Skincare Consumers in Indonesia (Journal of Innovation in Academia, 2025)
Based on social cognitive theory, this study examines the influence of content marketing and electronic word-of-mouth (e-WOM) on the purchasing decisions of skincare consumers. It also investigates whether the effects of content marketing and e-WOM on purchasing decisions differ significantly between pure online shoppers and webroomers. A quantitative approach was used to examine the causal relationship among the study variables. Likewise, cross-sectional data were purposively collected from 298 skintific users in Sumenep Regency, Indonesia. SmartPLS 4.0 was employed for analysis. This study found that both content marketing and e-WOM significantly influence skincare purchasing decisions, with no notable difference between pure online shoppers and webroomers. The results suggest that digital content and peer-generated reviews have become central touchpoints in high-involvement product decisions, transcending the physical-digital shopping divide. Findings reveal converging digital consumer behaviors, urging brands to adopt consistent, credible, and engaging digital strategies to build trust and drive purchase intentions.